Sistem Informasi Untuk Supply Chain Berkelanjutan Berbasis Pengetahuan - Mustafid, Mustafid (Universitas Diponegoro, 2015)
Information systems and supply chain has a strategic role to manage, measure and improve business performance with a sustainable competitive advantage. This paper aims to design the basic theoretical concepts of information systems for a enterprise knowledge-based sustainable supply chain. These systems in the form of a sustainable supply chain information system designed based enterprise resource knowledge and directed in accordance with the objectives and indicators of business performance in a sustainable by taking into account environmental, economic and society. Concepts theoretical basic of this system can be used as a basic for research development and application in the field of information systems and supply chain sustainability. The application of this system can be used to help management in managing and optimizing enterprise knowledge resources in accordance with the potential of the enterprise in order to improveÂ business performance overallÂ and sustainability.Â